Paul Huf : People. (Amsterdam : Koninklijke Ahrend, 1999)
A selection from the meetings of Paul Huf and Koen F.E. van Musschenbroek Gréve with people photographed for the Annual Reports of Koninklijke Ahrend = Een keuze uit de ontmoetingen van Paul Huf en Koen F.E. van Musschenbroek-Gréve met personen voor de Jaarverslagen van Koninklijke Ahrend.
biografie
Engels
Nederlands
boek
Keywords: Huf, Paul